Analisis Kebutuhan Pengembangan Media Pembelajaran Board Game Aqidah Akhlak Berbasis Pendidikan Karakter di Taman Pendidikan AlQur’an Masjid Ikhwanul Muslimin Kota Padang - Usral, Zilham; Alfurqan, Alfurqan (ALSYS, 2023)
This research aims to analyze the need for developing learning media in the form of Aqidah Akhlak-based board games that support character education at the TPQ Muslim Ikwanul Mosque, Padang City. The research method used is qualitative with a case study approach. Data was collected through interviews, observation and documentation from one supervisor, one teacher and seven students at the TPQ Ikwanul Muslimin Mosque. Data analysis was carried out using the Miles and Huberman approach which consists of four stages: data collection, data reduction, data presentation, and drawing conclusions. Based on the results of media needs analysis, analysis of student characteristics and curriculum analysis, it shows that the current use and utilization of learning media is still not optimal at TPQ Mosque Ikwanul Muslimin. Therefore, it is necessary to develop learning media in the form of the Aqidah Akhlak board game based on Character Education. This recommendation is based on the results of analysis of student characteristics, curriculum analysis, and relevant considerations. It is hoped that this research can contribute to improving the quality of learning at the TPQ Ikwanul Muslimin Mosque and support the formation of strong character in students through innovative approaches to learning media.